Bacteriological analysis of commercial cat canned food - Sabuan, Nurhidayati; Sabri, Jasni; Abdullah, Faez Firdaus Jesse (2010)
In any attempt to produce safe food products for animal consumption, canned food should be processed with regards to canned food safety. Commercial cat canned food of three different brands were analyzed for bacterial contamination. Bacteriology results showed that all canned foods tested were free of contamination. However when the cat canned food were exposed to room temperature, Proteus mirabilis, Staphylococcus intermedius, Bacillus spp. and Arcanobacterium spp. were isolated as early as 24 hours post exposure. Nevertheless, the isolation of bacteria from contaminated processed foods in this study in cat canned food differed from previous study of contamination in dog foods and human canned food 40% of cat owners who reported their cats developed diarrhea especially when their cats consumed cat canned food of ocean fish flavor could be due to improper food handling of opened unfinished canned food. This study highlights the importance of creating awareness of proper food handling to pet owners by veterinarian and animal health care personnel.